Upaya Menekan Penyakit ISPA dengan Pelatihan Deteksi Sedini Mungkin di Puskesmas Maccini Sawah - Sanghati Sanghati; Yantimala Yantimala; Basmalah Harun; Nur Annisa Fitri; Ilyas Pobi (Universitas Muhammadiyah Manado, 2021)
Acute Respiratory Tract Infection is an upper or lower respiratory tract disease that is usually contagious and can cause a wide spectrum of disease ranging from mild to severe and fatal infections, depending on the pathogen causing environmental factors and host factors. Transmission of acute respiratory infections is very dangerous, especially for babies and toddlers. It is necessary to reduce the incidence of transmission of acute respiratory infections as a form of prevention. Proper early recognition to detect symptoms of acute respiratory infections can be a way to prevent delays in treating the disease and prevent possible transmission. The method used is to provide counseling and training related to early detection of acute respiratory tract infections. After providing counseling to better understand the disease, one of the early detection methods chosen after recognizing the symptoms experienced is by counting the respiratory frequency. The results of implementing this community service include increasing knowledge to recognize and detect acute respiratory infections so that they can be treated immediately and appropriately.